A Monte Carlo Simulation of the Tax Burdens and Impacts Associated With Common Intergenerational Family Farm Transfer Strategies - Rosacker, Kirsten M.; Rosacker, Robert E.; Fingland, Sean (Journal of Applied Business and Economics, 2023)
This paper utilizes a Monte Carlo approach to simulate intergenerational farm property transfers within the context of four common succession strategies across a series of ordinary income and capital gain tax rates. Ordinary income/expenses accompany these intergenerational transfers in the form of interest income and the potential for depreciation recapture and capital gain income for all sales between the parties where transaction prices exceed basis and financing is utilized. Finally, post-transfer depreciation charges for the successor may accompany the usage of the family farm assets exchanged. The findings highlight the fact that transfers through estates represent the best pure tax outcomes (lowest aggregate tax burden), while sales transactions involve the highest tax burden. The conclusion is that it would be prudent and well-advised for everyone contemplating or engaging in intergenerational family farm transfers to ensure that tax considerations represent a focus for evaluating, determining, and selecting the best timing and course of action.